Iron(II)‐Catalyzed Cyanoalkylsulfonylation/Annulation Cascades toward Functionalized Sulfonylated Pyrrolidone Alkylnitriles. Issue 8 (13th April 2023) - Huang, Jiapian; Xu, Shujuan; Zhu, Jia; Chen, Zhiyuan
Abstract: Under heating conditions, an iron(II)‐catalyzed cascade cyanoalkylsulfonylation/cyclization reaction is developed to produce cyanoalkylsulfonylated pyrrolidones bearing with a free CN moiety. This alkyl radical disconnection and cascade annulation protocol enjoys chemo‐ and regioselectivity with the tolerance toward a range of functional groups. The reactive cyanoalkyl radical, which was originated from the ring‐opening reaction of a cyclic imine radical, was found to be capable of capturing the in‐situ generated "SO2 " species from DABSO, thus leading to the production of a cyanoalkyl sulfonyl radical and the subsequent alkene annulation sequences. Abstract :